Mutagenic effectiveness and efficiency of sodium azide versus ethyl methanesulfonate in maize: Induction of somatic mutations at the yg2 locus by treatment of seeds differing in metabolic state and cell population - Conger, B.V.; Carabia, J.V. (Mutation Research/Environmental Mutagenesis and Related Subjects, 1977)
This study was conducted to compare the effectiveness and efficiency of sodium azide (NaN 3) and ethyl methanesulfonate (EMS) for inducing somatic mutations at the yg 2 locus in maize seeds of two different metabolic states and cell populations. Dormant or presoaked (72 h at 20°C) seeds heterozygous for yg 2 locus were treated with different concentrations either EMS or NaN 3. The cell populations with respect to the percentage of cells in G 1, S, G 2, and M were also determined for seeds of the two metabolic states. Dormant seeds possessed a higher percentage of cells in G 1 and the presoaked seeds a higher percentage of cells in S, G 2, and M. The frequency of yg 2 sectors in leaves 4 and 5 increased with increasing concentration of both mutagens in both dormant and presoaked seeds. Both mutagens were more effective and efficient in the presoaked seeds. NaN 3 was more effective than EMS in terms of number of sectors induced per unit of dose. However, EMS was more efficient as determined by sectors induced per unit of seedling injury and clearly had the ability to induce much higher sector frequencies (more than 10 times greater) than NaN 3. The low ability of NaN 3 (compared to EMS) to induce mutant sectors may be related to the cells not being treated at the optimum time during cell cycle, but it is more likely due to its low effectiveness for inducing chromosomes aberrations.